Design dual input power system stabilizer for a multi-machine system based on focused- time- delay neural network - Quyền Huy Ánh; Nguyễn Ngọc Âu; Nguyễn Vũ Phương Thảo (Journal of Technical Education Science, 2013)
In this paper, a novel technique for real-time tuning of the parameters of the dual input power system stabilizers (FTDNN-PSS) updated by error BP method in a multi machine system using Focused- Time- Delay Neural Network is presented. To simulate and evaluate the performance of Dual input FTDNN-PSS under wide variations in loading conditions such as three phase short-circuit on transmision line; light loading conditions; heavy loading conditions, the system response is compared with these cases where there is conventional power system stabilizer (PSS Kundur). Simulation results demonstrate the effectiveness and robustness of dual input FTDNN-PSS in a multi-machine system, ensuring that generators quickly remain stable at a new position with better and faster damping and larger operating conditions.